Pengaruh Struktur Modal dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan Melalui Moderasi Profitabilitas - Redemptus Andre Anggara Prasetya; Clara Susilowati (Jurnal Proaksi, 2024)
Financial performance mirrors company accomplishments through effective asset management. Researchers hypothesize an interplay between profitability, capital structure, and sales growth, impacting financial performance. The aim and objective of this research is to determine the role of profitability in moderating the influence of capital structure and sales growth on financial performance. In this research, quantitative methods are used to collect and analyze data summarized in the form of numbers and statistics to understand phenomena, relationships or patterns in the population studied. The population of this research was 67 companies and was selected using a purposive method to produce 230 sample data from 46 companies. The data analysis used in this research is moderated regression analysis. After data analysis, it can be concluded that sales growth cannot significantly affect financial performance. Capital structure also cannot significantly influence financial performance. Meanwhile, profitability has proven capable of strengthening the relationship between sales growth and capital structure on financial performance.